Relationship between electroretinogram records and clinical signs in patients with various stages of primary open-angle glaucoma (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Lately, a much attention has been paid to studying the retina in patients with primary open angle glaucoma (POAG). The essence of the process has been reported to be an accelerated death of ganglion cells in the retina and retinal axons, comprising the optic nerve, as well as neuroglia, providing optic nerve repair, involved in the pathological process. The purpose of the present paper was to study the relationship between electroretinogram records and clinical signs in patients with various stages of primary open-angle glaucoma. Material and Methods. 358 eyes of 186 patients with POAG and patients with POAG to be confirmed underwent complex clinical and neurophysiological examination at SI “The Filatov Institute of Eye Diseases and Tissue Therapy”. Results. It is known that negative a-wave potential displays response in photoreceptor cells of the outer retinal layer and positive b-wave characterizes bioelectrical activity of the second order neurons of the retina (bipolar cells with possible contributions of horizontal and amacrine cells) and Muller glia cells whilst 30 and more Hz stimulation can be responded by cones only. Therefore, according to our data, initial glaucoma patients have lesions in outer and inner retinal layers as early as initial stages of glaucomatous process. The most apparent pathological changes in neurophysiological process are observed in photoreceptor cells of the outer retinal layer, including cone elements of the retina.Conclusion. As pathological process is growing, more correlations are observed; therefore, pathological changes affect corresponding retinal elements and result in a decrease of differential light sensitivity of the retina, central visual acuity defects, an increase of IOP, and a decrease of optic nerve excavation width; and this is the evidence of pathogenetic character of these neurophysiological alterations in the retina.
Keywords: primary open-angle glaucoma; electroretinogram; photoreceptor cells; inner retinal layer